Impact of Immigration Policies on Economic Growth in Germany - Braun, Felix (Journal of Public Policy and Administration, 2024)
Purpose: To aim of the study was to analyze the impact of immigration policies on economic growth in Germany. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Germany's immigration policies have had a significant impact on its economic growth. These policies have facilitated the influx of skilled labor, which has helped to address the country's demographic challenges, particularly the aging population and labor shortages in key sectors. Immigrants have contributed to the labor market by filling both high-skilled and low-skilled jobs, boosting productivity and innovation. Additionally, immigration has increased consumer demand, further stimulating economic growth. Unique Contribution to Theory, Practice and Policy: Human capital theory, dual labor market theory & endogenous growth theory may be used to anchor future studies on the impact of immigration policies on economic growth in Germany. Implement comprehensive language and vocational training programs for refugees and low-skilled immigrants to facilitate their economic integration and productivity. Formulate balanced immigration policies that address sector-specific labor demands without disadvantaging native workers.